Time Pro‐rata Matching: Evidence of a Change in LIFFE STIR Futures. Issue 6 (12th January 2015) - Aspris, Angelo; Foley, Sean; Harris, Drew; O'Neill, Peter
Abstract: Matching algorithms are important for well‐functioning financial markets. This paper examines the 2007 change by LIFFE, to move from pure pro‐rata to time pro‐rata allocation for the Euribor, Short Sterling, and Euroswiss futures contracts. We show that the removal of pure pro‐rata matching reduces market depth but suggest that this outcome improves execution quality for market participants. Our results are consistent with suggestions in the literature that the former regime creates incentives for traders to "drown" the order book with large orders and that the addition of a time element to this algorithm alters their behavior. We provide evidence that traders increase the amount of order splitting in the new framework, consistent with local optimizing, but argue that this may hinder overall market efficiency. © 2015 Wiley Periodicals, Inc. Jrl Fut Mark 35:522–541, 2015